The Effect of Leader Member Exchange and Perceived Organizational Support on Organizational Citizenship Behavior through Job Satisfaction (Study at Branch Office of PT Bank Negara Indonesia (Persero) Tbk, West Sumatra) - Agnes Lovita Monna; Hendra Lukito; Donard Games (Jurnal Mantik, 2022)
Employees with Organizational Citizenship Behavior will encourage their best ability to produce the best output for the benefit of the organization. This study aims to analyze the factors that influence Organizational Citizenship Behavior and the mediating role of Job Satisfaction. The population in this study were all employees of BNI at the Solok, Payakumbuh, and Bukittinggi branch offices, with a total sample of 103 people. The source of this research data is primary data collected through questionnaires. Structural equation modeling method (PLS-SEM) was used to analyze the data. The results of this study indicate that Leader Member Exchange and Perceived Organizational Support have a positive effect on Organizational Citizenship Behavior, but Job Satisfaction has no effect on Organizational Citizenship Behavior. Leader Member Exchange positively affects Job Satisfaction, but Perceived Organizational Support fails to affect Job Satisfaction. This study found that job satisfaction did not mediate the relationship between Leader Member Exchange and Perceived Organizational Support on Organizational Citizenship Behavior.